Study of seed agitation in the fluid of a hydropneumatic precision seeder - Pastukhov, Valerii; Пастухов, Валерій; Boiko, Vladyslav; Бойко, Владислав; Tesliuk, Hennadii; Теслюк, Геннадій; Ulexin, Vasyl; Улексин, Василь; Kyrychenko, Roman; Кириченко, Роман (Український державний університет залізничного транспорту, 2020)
One of the most responsible operations in the cultivation of vegetables includes seeding. Its timing and quality largely determine the quality of sprouts, yield and crop morbidity. The emergence of sprouts can be accelerated and their uniformity can be improved by using hydraulic seeding of germinated seeds. The operation of hydraulic seeders can be divided into main stages: agitation of seeds in a liquid, selection, and dosage of seeds, seeding in the seedbed. The process of seed agitation in a liquid, that is, obtaining a fluidized bed with required seed concentration in the intake chamber of the hydropneumatic precision seeder was considered. The process of seed agitation in the liquid is performed in different ways: bubbling or the use of mechanical stirrers. Each of them requires the use of energy-intensive actuators. A method of seed agitation in a liquid was proposed. It makes it possible to reduce energy consumption by means of agitation, not the entire volume but just the part that is in the zone of seed intake to the seed duct. According to the results of theoretical studies, it has been established that to ensure reliable and accurate seeding, the seed concentration should be in the range of 0.2–0.65 pcs/ml. Under such conditions, the charging process takes place without clogging the seed duct and at an acceptable speed of the seeder. The main factors influencing the formation of a set seed concentration were established: seed diameter, the height of the fluidized bed, flow speed in the intake chamber, the angle between walls of the intake chamber, fluid flow rate. According to the results of theoretical studies of the process of formation of a set seed concentration, limits of existence of the fluidized bed (h2=0.014 m, h1=0.07 m) and height of the seed duct (hH≈0.015–0.02 m) which will ensure reliable and prompt taking of seeds from the intake chamber for their further dosage and seeding. The main provisions of theoretical studies of the agitation process and formation of a set seed concentration were confirmed by experimental studies in a laboratory. Одна з найбільш відповідальних операцій при вирощуванні овочів включає посів. Його терміни та якість значною мірою визначають якість паростків, урожайність та захворюваність врожаю. Виникнення паростків можна прискорити та покращити їх однорідність за допомогою гідравлічного висіву пророщеного насіння. Роботу гідравлічних сівалок можна розділити на основні етапи: перемішування насіння в рідині, відбір і дозування насіння, висів на посівне ложе. Розглянуто процес перемішування насіння в рідині, тобто отримання псевдозрідженого шару з необхідною концентрацією насіння у впускній камері гідропневматичної прецизійної сівалки. Процес перемішування насіння в рідині виконується різними способами: барботування або використання механічних мішалок. Кожен з них вимагає використання енергоємних приводів. Запропоновано метод перемішування насіння в рідині. Це дозволяє зменшити споживання енергії за допомогою перемішування не всього об’єму, а лише тієї частини, яка знаходиться в зоні надходження насіння в насіннєвий проток. За результатами теоретичних досліджень встановлено, що для забезпечення надійного та точного висіву насіння концентрація насіння повинна бути в межах 0,2–0,65 шт / мл. За таких умов процес завантаження відбувається без засмічення насіннєвого каналу та з прийнятною швидкістю сівалки. Встановлено основні фактори, що впливають на формування заданої концентрації насіння: діаметр насіння, висота киплячого шару, швидкість потоку у впускній камері, кут між стінками впускної камери, швидкість потоку рідини. За результатами теоретичних досліджень процесу формування заданої концентрації насіння, меж існування киплячого шару (h2 = 0,014 м, h1 = 0,07 м) та висоти насіннєвої протоки (hH≈ 0,015–0,02 м) що забезпечить надійне та оперативне взяття насіння з приймальної камери для подальшого їх дозування та висіву. Основні положення теоретичних досліджень процесу перемішування та формування заданої концентрації насіння були підтверджені експериментальними дослідженнями в лабораторії
Вивчення перемішування насіння в рідині гідропневматичної прецизійної сівалки
Keywords: germinated seeds; пророщене насіння; hydroseeder; гідросівалка; precision seeding; точне висівання; fluidized bed; псевдозріджений шар; seed concentration; концентрація насіння; porosity; пористість